Antimicrobial Activity Test of Ethanol Extract of Forest Betel Leaves (Piper aduncum L.) - Diza Sartika; Epi Supri Wardi; Dyah Komala Putri; Miftahur Rahmi (UIN Sulthan Thaha Saifuddin Jambi, 2025)
Abstract. Forest betel (Piper aduncum L.) is a herb that is easily found as a wild plant known to contain secondary metabolite compounds, namely flavonoids, tannins, steroids, phenolics and alkaloids. The purpose of this study was to determine the antimicrobial activity of ethanol extract of forest betel leaves (Piper aduncum L.) against Escherichia coli and Staphylococcus aureus bacteria and Candida albicans fungi as well as the minimum inhibitory concentration (MIC) and minimum bacteriside concentration (MBC) of the extract. The method used in the activity test is the Kirby-Bauer method and in the MIC and MBC tests using the optical density (OD) measurement method using a UV / VIS spectrophotometer. The results of testing antimicrobial activity against Escherichia coli bacteria have the largest average inhibition zone at a concentration of 20% (7.86 mm) which is included in the weak category. While in Staphylococcus aureus and Candida albicans, the 80% extract concentration has the largest average inhibition zone, 12.72 mm and 18.54 mm respectively, which is included in the moderate category. Testing the minimum inhibitory concentration (MIC) of the extract against the test microbes showed that in all three test microbes the MIC was obtained at a concentration of 10% extract. testing then continued with the minimum bacteriside concentration (MBC) there were no results because all concentrations on all test microbes showed microbial growth.